The effect of the electric pulse polarity on CO(2) reforming of CH(4) using dielectric barrier discharge - Lee, Hwaung; Lee, Chung-Hun; Choi, Jae-Wook; Song, Hyung Keun (AMER CHEMICAL SOC, 2007)
Methane conversion using an electric discharge has been studied for many years. Recently, many research groups have developed a high-frequency pulsed plasma reaction for methane conversion to higher hydrocarbons and synthesis gas. The CO(2) reformation of methane to synthesis gas has also attracted considerable interest as a method of utilization of the greenhouse gases, CO(2) and CH(4), which occupy most of man-made greenhouse gases. In this study, the influence of pulse polarity of the pulse power supply on methane and carbon dioxide conversions has been investigated using a cylindrical-type dielectric barrier discharge (DBD) reactor. For this purpose, two kinds of power supply were compared, that is, a bipolar pulse power supply and a unipolar pulse power supply. The input voltage and the power frequency were used as operating variables. The energy efficiency of the bipolar pulse power was compared with that of the unipolar pulse power for the CO(2) reformation of methane using DBD. Increasing the voltage and frequency resulted in an increase of the conversion of CH(4) and CO(2). The selectivity of CO and C(2) products was decreased, while the conversion of CH(4) and CO(2) increased with the electric power supply being increased. For the same amount of energy consumed, the bipolar pulse power was more effective than the unipolar pulse on the CH(4) reformation of the CO(2) reaction. The selectivity of the product was not affected by the pulse polarity.
Keywords: HIGHER HYDROCARBONS; CARBON-DIOXIDE; ATMOSPHERIC-PRESSURE; METHANE CONVERSION; PARTIAL OXIDATION; NONTHERMAL PLASMA; PATHWAYS; REACTOR; OXYGEN; GASES